Desempenho e digestibilidade em novilhos Nelore e Nelore x Angus alimentados com dietas de grãos de milho inteiro e bagaço de cana - Rodrigues, Aline de Castro (2018)
The objective of this study was to evaluate performance, carcass traits, ingestive behavior and digestibility of nutrients in Nellore and Nellore × Angus steers fed whole shelled corn diets, with or without sugarcane bagasse. Thirty-two animals, with average BW of 353 ± 25.3 kg were housed in individual pens and used in a completely randomized design using a 2 × 2 factorial arrangement (2 breeds and 2 diets). One diet contained 80% whole shelled corn and 20% of a protein-mineral pellet (WSC). The other diet had 74% whole shelled corn, 20% protein-mineral pellet, and 6% of sugarcane (WSCB). Feeding period was 116 d, with 20 d of adaptation period and 96 d of experimental period. The digestibility trial occurred after 65 days of the experimental period, using total feces collection for three days. Feed offered was recorded daily, and the feed remaining on the following day was weighed back to calculate DMI. At the end of the feedlot, steers were slaughtered using cerebral concussion and slitting of the jugular vein, and then carcass traits were measured. Nellore × Angus steers had greater final BW, DMI, ADG, backfat thickness (P < 0.05). However, Nellore steers had greater yield carcass (P <0.01). Steers fed WSCB had greater DMI and less variation (P < 0.01). Animals fed WSC spent less time ruminating and more time on idleness (P < 0.01) and ingesting water (P = 0.03) than animal fed WSCB. The rate of rumination/DMI, intake of NDF (kg) and NDFI:DMI ratio (P < 0.01) were greater for animals fed WSCB. Nellore steers spent more time ruminating, had greater rate of rumination/DMI (P < 0.01) and rate of rumination/NDF (P = 0.01). Nellore × Angus steers had greater intake of NDF (P = 0.01) and digestibility coefficients of NDF (P = 0.04) and tendency for greater digestibility of DM, OM, CP and TDN (P < 0.10). Animal fed WSC had greater digestibility coefficients of DM, OM, TDN, NFC (P < 0.01), CP, EE and NFC (P < 0.05). There was no breed (P = 0.29) and diet (P = 0.21) effect on starch digestibility. The activity of α-amylase tended to be greater in Nellore steers (P = 0.07). In conclusion, Angus × Nellore steers have greater ADG than Nellore, but they are not more efficient. The use of bagasse in WSC diets increases DMI and therefore ADG in feedlot steers. The use of fiber sources in low quantities, such as sugarcane bagasse is indicated in WSC diets, as it increases DMI and ADG without change feed efficiency or carcass characteristics. Nellore x Angus steers has greater performance with WSC diets than Nellore steers because they have a greater capacity for digestion of this diet and its nutrients.